anonymous
  • anonymous
Find the solution to the equations. 3x - y = -4 x + y = 0 (0, 0) (-1, 1) (1, -1)
Algebra
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
Jamierox4ev3r
  • Jamierox4ev3r
you can solve this problem using substitution. first, solve the second equation for y. basically, we want to isolate the "y" variable here
Jamierox4ev3r
  • Jamierox4ev3r
@Sydney77 let me know if you understand :)
anonymous
  • anonymous
Simple

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

ageta
  • ageta
I will try to solve your system of equations. 3x−y=−4;x+y=0 Step: Solve 3x−y=−4 for y: 3x−y+−3x=−4+−3x(Add -3x to both sides) −y=−3x−4 (Divide both sides by -1) y=3x+4 Step: Substitute (3x+4) for y in x+y=0: x+y=0 x+3x+4=0 4x+4=0(Simplify both sides of the equation) 4x+4+−4=0+−4(Add -4 to both sides) (Divide both sides by 4) x=−1 Step: Substitute (−1) for x in y=3x+4: y=3x+4 y=(3)(−1)+4 y=1(Simplify both sides of the equation) Answer: y=1 and x=−1

Looking for something else?

Not the answer you are looking for? Search for more explanations.